Pengaruh Model Pembelajaran Debat Aktif Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X di SMA Negeri 1 Bonepantai - Della Agustina Djalil; Radia Hafid; Melizubaida Mahmud; Roy Hasiru; Sudirman Sudirman (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to examine the effect of the Active Debate Learning Model on students’ learning motivasion in the Economics subject for Grade X at SMA Negeri 1 Bonepantai, Bonepantai Subdistrict, Bone Bolango Regency. The research employed a quantitative method, whit a total of 94 student respondentfrom tree classes: X-1,X-2, and X-3.The primary instrument used in this study was a questionnaire. The collected data were analysed using simple linear regression and a normality test, which yielded a significance value of 0.059. Since this value is greater than the 5% alpha level (0.05), it can be concluded that the residual are normally distributed. Additionally, the correlation coefficient test resulted in a value of 0.938, indicating a very strong relationship between the active debate learning model (X) and students’  learning motivation (Y) in grade X at SMA Negeri 1 Bonepantai, Bonepantau Subdistrict, Bone Bolango Regency.